Building The Character of Islamic Youth Through JASBON Activities at Kebonagung Hamlet of Nganjuk Regency, East Java - Moh. Badrus Solichin; M. Imam Musyafa’ Ali; Asep Maulana (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
The phenomenon of the association of young people today is getting wild and out of control. Relying more on lust than looking for the best possible identity to achieve God's pleasure. To build the character of Islamic youth, a da'wah institution is needed to instill Islamic values ​​and morals in the younger generation. JASBON (Jam'iyyah Sholawat Berzanji Kebonagung) is one of the da'wah institutions that has programmed support for increasing the religiosity of young people through the reading of shalawat, al-barzanji and tahlil, which are carried out regularly accompanied by Islamic music so that it can attract worshipers to join the Assembly's activities. This study uses a qualitative method that produces descriptive data in the form of written or spoken words from people and observable behavior. Data collection techniques used are observation, documentation, and interviews. The number of respondents in this study was ten men. The results showed that JASBON (Jam'iyyah Sholawat Berzanji Kebonagung) had tried to build the character of Islamic youth both from inside and outside the village and even outside the district through the cultivation of values, morals, and religious routines.